2018
DOI: 10.1016/j.buildenv.2018.03.046
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the effect of different starting room temperatures on occupant comfort in Danish summer weather

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Occupants may have experienced a cold thermal sensation during their commuting time early in the morning, which changed along the day. This result is in agreement with the study of Bourdakis et al [34], which showed that the preferred temperatures of occupants were lower after commuting to work due to higher metabolic activity levels. This suggests that there is a short-term physiological adaptation process when people arrive at their work place in the morning that should be taken into account in thermal comfort assessments.…”
Section: Discussionsupporting
confidence: 93%
“…Occupants may have experienced a cold thermal sensation during their commuting time early in the morning, which changed along the day. This result is in agreement with the study of Bourdakis et al [34], which showed that the preferred temperatures of occupants were lower after commuting to work due to higher metabolic activity levels. This suggests that there is a short-term physiological adaptation process when people arrive at their work place in the morning that should be taken into account in thermal comfort assessments.…”
Section: Discussionsupporting
confidence: 93%
“…However, the temperature in their study remained the same so that thecombined effect of temperature and metabolic rate transients was not explored. Recently, several other studies [19][20][21][22][23][24] have examined thermal transients induced by both temperature and metabolic rate, but they focused on effective ways to alleviate thermal discomfort induced by exercise in the heat, rather than investigating the underlying mechanism of human thermal responses under such conditions.…”
Section: Wet Skin Wettednessmentioning
confidence: 99%
“…The sample frame consists of 76 valid questionnaires comprising 30 bank staffers and 46 worshipers. Recent studies [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] have documented the negative effects of sick building syndrome on human health across climes. The survey instrument was administered by hand and consists of four parts.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%